Determinants of disability in cervical dystonia. (November 2016) - van den Dool, J.; Tijssen, M.A.J.; Koelman, J.H.T.M.; Engelbert, R.H.H.; Visser, B.
Abstract: Background: Cervical dystonia (CD) is characterized by involuntary muscle contractions causing abnormal postures and/or twisting movements of the head and neck. These motor symptoms can have a major impact on disability. Treatment with botulinum toxin injections aims to reduce motor symptoms, and therefore disability. Despite motor improvements, many patients still experience difficulties with performing daily life activities. To optimize treatment, other factors that determine disability should be identified. Objective: To explore and identify clinical characteristics that relate to disability in CD. Methods: Data on disability, severity of dystonia, anxiety, depression, pain and quality of life of 96 CD patients was analyzed with a principal component analysis (PCA). Multiple regression analysis was performed to determine which components derived from the PCA explain most of the variance in disability. Results: PCA revealed five components (disability, psychiatric features, pain, physical function and severity of dystonia), explaining 74.4% of the variance in disability. Multivariate association between disability and the other components was statistically significant (R 2 change 0.433, F change (4–86) = 22.39, p = .000). Psychiatric features had the largest contribution to disability (standardized beta = 0.555, p = 0.000) followed by pain (standardized beta = 0.232 p = 0.004). Physical functioning (standardized beta = 0.059 p = 0.507) and severity of dystonia (standardized beta = −0.001 p = 0.991) had no significant contribution. Conclusions: In CD patients, psychiatric features and pain are important determinants of disability. Interventions to reduce psychiatric problems and pain should have a more prominent role in the treatment of CD patients in order to improve disability levels. Highlights: Treatment of cervical dystonia is mainly aimed at reducing motor symptoms with botulinum toxin injections. Many CD patients still encounter difficulties performing daily life activities, despite motor improvements. Psychological factors and pain make substantial contributions to disability in cervical dystonia. To reduce disability levels, interventions aimed at psychological problems and pain should have a more prominent role.